2019
DOI: 10.21873/invivo.11539
|View full text |Cite
|
Sign up to set email alerts
|

shRNA-WT1 Potentiates Anticancer Effects of Gemcitabine and Cisplatin Against B16F10 Lung MetastasesIn VitroandIn Vivo

Abstract: Background/Aim: High expression level of Wilm's tumor gene (WT1) in several types of tumors appears to confer disruption of apoptosis and resistance to chemotherapeutic drugs, and correlate with poor outcome. The aim of this work was to determine if down-regulation of WT1 expression results in decreased cell proliferation and the increased action of different types of drugs, both in vitro in B16F10 cells, and in vivo in C57BL/6 mice. Materials and Methods: Inhibition of cell proliferation by short hairpin RNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 38 publications
1
7
0
Order By: Relevance
“…Initial studies focused on gemcitabine dose response at 37 °C to evaluate the impact of 48 hour exposure to low (subclinical) concentrations of 10, 100, 500, 1,000, and 5,000 nM on cell viability (Figure 4). These concentrations equate to 0.11, 0.56, 1.11, 5.57, and 55.5 mg/m2, respectively, all of which were significantly lower than the clinical dose (800-1000 mg/m2) when applied as a single agent, but are in line with published in vitro concentrations [56][57][58]. Sample assessment following a 48 hour treatment revealed that sample viability decreased to 76% (±2.0), 81% (±1.4), 76% (±1.8), 70% (±2.0), and 56% (±2.8) of non-treated controls for 10, 100, 500, 1,000, and 5,000 nM gemcitabine, respectively (Figure 4).…”
Section: Assessment Of the Combination Of Gemcitabine And Freezingsupporting
confidence: 86%
“…Initial studies focused on gemcitabine dose response at 37 °C to evaluate the impact of 48 hour exposure to low (subclinical) concentrations of 10, 100, 500, 1,000, and 5,000 nM on cell viability (Figure 4). These concentrations equate to 0.11, 0.56, 1.11, 5.57, and 55.5 mg/m2, respectively, all of which were significantly lower than the clinical dose (800-1000 mg/m2) when applied as a single agent, but are in line with published in vitro concentrations [56][57][58]. Sample assessment following a 48 hour treatment revealed that sample viability decreased to 76% (±2.0), 81% (±1.4), 76% (±1.8), 70% (±2.0), and 56% (±2.8) of non-treated controls for 10, 100, 500, 1,000, and 5,000 nM gemcitabine, respectively (Figure 4).…”
Section: Assessment Of the Combination Of Gemcitabine And Freezingsupporting
confidence: 86%
“…Numerous studies have shown that shRNA is a viable method to treat various tumors and cancers [15,22,23]. In tumors such as Wilm's Tumor, a form of kidney cancer that primarily manifests in children, apoptosis of cancerous cells has been acheived using shRNA to suppress critical exons of the WT1 gene in in vitro and in vivo studies [22,24].…”
Section: Rnai Therapy In Treatments Of Acp Shrnamentioning
confidence: 99%
“…In tumors such as Wilm's Tumor, a form of kidney cancer that primarily manifests in children, apoptosis of cancerous cells has been acheived using shRNA to suppress critical exons of the WT1 gene in in vitro and in vivo studies [22,24]. In a study analyzing the effects of shRNA on other WT1 cell lines, a gene that has been found to code for many cancers such as leukemia, lung cancer, and ovarian cancer, plasmids containing shRNA were transfected into B16F10 cells, a cell line associated with melanoma, and incubated for 72 hours [15,22]. In this cell line, shRNA-WT1 was highly effective at decreasing cell viability compared to the control group suggesting that shRNA treatment may be effective for reducing tumor burden [22].…”
Section: Rnai Therapy In Treatments Of Acp Shrnamentioning
confidence: 99%
See 1 more Smart Citation
“…High expression of WT1 is described in leukemias and in solid tumors and it seems correlated to the chemoresistance and poor outcome. Interestingly, inhibition of cell proliferation by shRNA-WT1, cisplatin, and gemcitabine in B16F10 cells induces cell death and potentiates the action of anticancer drugs by inducing synergistic effects both in vitro and in vivo (Zapata-Benavides et al, 2019). Although WT1 could be expressed by Spitz naevi and in up to one third of dysplastic naevi, it is considered as a diagnostic tool in melanoma diagnosis (Wilsher and Cheerala, 2007).…”
Section: Wt1mentioning
confidence: 99%